Analysis of fatty acid composition of anaerobic rumen fungi - Koppová, Ingrid; Novotná, Zuzana; Štrosová, Lenka; Fliegerová, Kateřina (Folia microbiologica, 2008)
The fatty acid (FA) composition of fresh mycelia of anaerobic rumen fungi was determined. The fatty acids methyl esters (FAME) of six strains belonging to four genera (Neocallimastix, Caecomyces, Orpinomyces, Anaeromyces) and one unknown strain were analyzed by gas chromatography. All studied fungi possess the same FAs but differences were found in their relative concentrations. The FA profile of anaerobic fungi comprises carbon chains of length ranging from 12 to 24; the most common fatty acids were stearic (C(18:0)), arachidic (C(20:0)), heneicosanoic (C(21:0)), behenic (C(22:0)), tricosanoic (C(23:0)) and lignoceric (C(24:0)) with relative amount representing >4% of total FA. Significant differences were determined for heptadecanoic, oleic, behenic and tricosanoic acids. Rumen anaerobic fungi can contain very long chain fatty acids; we found unsaturated fatty acids including cis-11-eicosenoic (C(20:1)), cis-11,14-eicosadienoic (C(20:2)), erucic (C(22:1n9)), cis-13,16-docosadienoic (C(22:2)) and nervonic (C(24:1)) acids in very small amounts but their presence seems to be unique for anaerobic fungi.
Keywords: Anaerobiosis; mastné kyseliny; Species Specificity; Mycological Typing Techniques; Rumen; anaerobióza; Fatty Acids; zvířata; Animals; houby; mykologické určovací techniky; bachor; Fungi; druhová specificita